Hakikat Manusia dan Potensi Ruhaninya dalam Pendidikan Islam: Sebuah Kajian Ontology - Aziz, Abd. (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Human being is actually a combination of some inseparable parts such as body and mind. If one of the parts is missing, such creature is not a human being anymore. To reach a comprehensive human being or it also called as insan kamil, an education is a must. Through education, the balanced role between body and mind can be attained.